the Effect of Special Exercises in the Speed of Compatibility Abilities and Accuracy in the Development of Some Basic Skills in Youth Football - Sami Yousif Malik, Faris; Najeeb Asleawa, Wesam; Kadhim Ali, Naji (International Journal of Psychosocial Rehabilitation, 2020)
The consensual exercise is building a positive impact on the development of basic skills for youth football players. The progression of the compatibility capability training swelled quickly, accurately, and with different intensities, low and high, which had a great role in the mechanism of professional performance in football. The intermarriage of exercises between the skills used in speed training and harmonic accuracy has a positive effect on the level of skill development in football. Emphasizing the special harmonic exercises as it leads to the development of the speed and accuracy of the skilled performance of football. There is a need to develop players through capacity building and other consensual exercises in a scientific manner, which has positive effects on the development of basic skills in football. There is a need to use different methods of exercises, consensual, and not rely on only one way.